PENGARUH PAKAN TAMBAHAN TEPUNG KEPALA UDANG DAN KACANG HIJAU (Vigna radiate L.) TERHADAP KANDUNGAN PROTEIN DAN BOBOT PADA IKAN NILA (Oreochromis niloticus) (Oreochromis niloticus) - Septiandi, Rigi; Febriani, Husnarika; Pima Sari Tambunan, Efrida (Universitas Cokroaminoto Palopo, 2025)
Shrimp head flour is processed from shrimp processing waste and used as an alternative feed that has a fairly high nutritional content. While mung bean flour is processed from the main ingredient of mung beans that have been semi-processed which have a fairly high vegetable protein content. The purpose of this study was to see whether the provision of additional feed of mung bean flour (Vigna radiata L.) and shrimp head flour affects the weight and protein content of tilapia (Oreochromis niloticus). The design used in this study was a completely randomized design (CRD) with 4 treatments on 20 tilapia. P0 = 100% commercial feed, P1 = 75% commercial feed, 20% shrimp head flour, and 5% mung bean flour, P2 = 50% commercial feed, 40% shrimp head flour, 10% mung bean flour, P3 = 25% commercial feed, 60% shrimp head flour, 15% mung bean flour. This study used two parameters, namely the weight of tilapia produced and the protein content of tilapia. Data analysis using one way ANOVA and continued with Duncan's further test. The results obtained in the addition of additional feed of green bean flour and shrimp head flour had a significant effect on the protein content of tilapia with a value of 15.26 (p = 0.000). The results of green bean flour affected the growth of tilapia weight with a value of 13.6% (p = 0.000). The most optimal feed in increasing the protein content and body weight of tilapia was in group P3.